Administration of a leptin antagonist during the neonatal leptin surge induces alterations in the redox and inflammatory state in peripubertal /adolescent rats. - Mela-Rivas, Virginia; Hernández, Oskarina; Hunsche, Caroline; Díaz, Francisca; Chowen, Julie Ann; De la Fuente, Mónica (Elsevier, 2017)
The importance of the neonatal leptin surge in rodents in neurodevelopmental processes has aroused curiosity in its implication in other physiological systems. Given the role of leptin in neuro-immune interactions, we hypothesized that the neonatal leptin surge could have an effect on the oxidative and inflammatory stress situations of both systems. We blocked the neonatal leptin surge by a leptin antagonist and measured several parameters of oxidative and inflammatory stress in the spleen, hypothalamus and adipose tissue of peripubertal/adolescent rats. The treated rats showed lower activity of several antioxidant enzymes in the spleen and their leukocytes released lower levels of mitogen-stimulated IL-10 and IL-13 and higher levels of TNF-alpha. In conclusion, the neonatal leptin surge may have a key role in the establishment of adequate redox and inflammatory states in the immune system, which is important for the generation of adequate immune responses and to obtain and maintain good health.
Keywords: Inflamación (Patología); Citoquinas; Inmunidad celular; Antioxidantes; Leptina - Antagonistas; Modelos animales en investigación; Antioxidant defenses; Leptin antagonist; Neonatal leptin; Peripubertal rats; Proinflammatory and anti-inflammatory cytokines